A wear-resistant metal composite cone and its preparation method

By injecting inert gas and covering the refined flux during the centrifugal casting process, the problems of slag inclusion and pores of the interface are solved, the interface strength and wear resistance are improved, the composite layer is peeled off and cracked, and the service life of the cone is extended.

CN116174674BActive Publication Date: 2024-12-13GUANGDONG INST OF NEW MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211678285.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-26
Publication Date
2024-12-13
Estimated Expiration
2042-12-26

AI Technical Summary

Technical Problem

In the prior art, the centrifugal casting method results in slag inclusion or pores at the interface, low interface strength, easy peeling of the composite layer, and easy cracks in the cast iron part of the high chromium alloy, affecting the composite effect.

Method used

Under the action of centrifugal force, high-chromium alloy cast iron is cast inert gas and a specific composition of refining flux is covered on its surface. Low-alloy steel is subsequently cast. The chemical components of the refining flux include Na2O, K2O, SiO2 and B2O3 to form Low melting point slag to eliminate pores and inclusions and improve interface bonding strength.

Benefits of technology

It achieves no slag inclusions and pores on the interface, high interface strength, the composite layer is not easy to fall off, and there are no cracks, which improves the wear resistance and service life of the cone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116174674B_ABST
    Figure CN116174674B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of preparation of bimetallic wear-resistant composite cones, and specifically relates to a wear-resistant metal composite cone and a preparation method thereof, the method comprising the following steps: under the action of centrifugal force, (1) high chromium alloy cast iron is cast into the cavity of a casting centrifuge, and an inert gas is introduced into the cavity; (2) the surface of the high chromium alloy cast iron liquid in the cavity into which the inert gas is introduced is then covered with a refining flux; (3) low alloy steel is subsequently cast; wherein the chemical composition of the refining flux includes, by mass percentage, 15-20% Na2O, 5-10% K2O, 10-15% SiO2, 2-5% resin, and 50-68% B2O3. The wear-resistant metal composite cone interface prepared by the present invention has no slag inclusions and pores, has high interface strength, and the composite layer is not easy to fall off and has no cracks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of bimetallic wear-resistant composite cones, and in particular relates to a wear-resistant metal composite cone and a preparation method thereof. Background Art

[0002] Cones such as grinding rollers, rolling rollers, and cones are indispensable consumable components for material crushing and grinding in roller crushers, rolling mills, cone crushers, etc. In order to improve the wear resistance of wear-resistant parts, bimetallic composite materials are often used. High-chromium alloy cast iron with high wear resistance is used in the service area of ​​the component (i.e. the outer surface of the cone) to improve wear resistance; high-strength and toughness low-alloy steel is used in the installation area (i.e. the inner layer of the cone) to improve the overall strength and toughness of the cone.

[0003] In the centrifugal casting method of the prior art, a high-chromium alloy cast iron melt is cast to a specific thickness of the cavity. The slags such as Al2O3, SiO2, and MnO in the high-chromium alloy cast iron melt have a light specific gravity. Under the action of centrifugal force, these slags cover the surface of the melt to form covering slag. At the same time, the air sucked into the cavity by the centrifugal force reacts with the elements such as Fe and Cr in the melt. In particular, the Cr element is highly active, generating chromium and iron oxides Cr2O3 and Fe2O3, which together with the above-mentioned covering slag form a slag layer. Due to the heat dissipation, the slag layer forms a hard slag shell; the heat of casting a low-alloy steel melt melts the hard slag shell, which floats to the upper end surface of the cone along the high-chromium alloy cast iron liquid surface under the action of centrifugal axial force, so that the low-alloy steel liquid and the high-chromium alloy cast iron liquid are in direct contact to form a metallurgical interface, thereby realizing the stable preparation of bimetallic composite materials.

[0004] However, the existing methods have the following defects: on the one hand, the centrifugal force causes the casting cavity to absorb a lot of slag; on the other hand, it is difficult to break the hard slag shell and float it, slag inclusions or pores appear on the interface, the interface strength is low, and the composite layer is easy to peel off during operation. For this reason, the casting temperature of the low-alloy steel melt is usually increased to melt the slag shell, but the low-alloy steel liquid and the high-chromium alloy cast iron liquid are often mixed. Moreover, due to the high casting temperature of the low-alloy steel and the large body shrinkage, the high-chromium alloy cast iron part is prone to cracks, affecting the composite effect. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the centrifugal casting method in the prior art, such as the appearance of slag inclusions or pores at the interface, low interface strength, and easy peeling of the composite layer during operation, and to provide a wear-resistant metal composite cone and a preparation method thereof. The wear-resistant metal composite cone prepared by the preparation method has no slag inclusions and pores at the interface, high interface strength, and the composite layer is not easy to fall off and has no cracks.

[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a wear-resistant metal composite cone, comprising the following steps: under the action of centrifugal force,

[0007] (1) casting high chromium alloy cast iron into a cavity of a casting centrifuge, and introducing an inert gas into the cavity;

[0008] (2) then covering the surface of the high chromium alloy cast iron liquid in the cavity into which the inert gas is introduced with a refining flux;

[0009] (3) subsequently casting low alloy steel;

[0010] The chemical composition of the refining flux includes, by mass percentage, 15-20% Na2O, 5-10% K2O, 10-15% SiO2, 2-5% resin, and 50-68% B2O3.

[0011] In some preferred embodiments, in step (1), the casting temperature of the high chromium alloy cast iron is 1400-1490°C.

[0012] In some preferred embodiments, in step (1), the centrifugal rotation rate of the cavity is 300-500 rpm.

[0013] In some preferred embodiments, step (1) further comprises: preheating the cavity wall to 200-300° C. before casting.

[0014] In some preferred embodiments, in step (1) and step (2), the flow rate of the inert gas introduced into the mold cavity is 8-50 L / min, preferably 40-50 L / min, and more preferably 48-50 L / min.

[0015] In some preferred embodiments, in step (2), the centrifugal rotation rate of the cavity is 100-200 rpm.

[0016] In some preferred embodiments, in step (2), the refining flux is introduced 40-80 seconds after casting the high chromium alloy cast iron, preferably 40-60 seconds, and more preferably 50-60 seconds.

[0017] In some preferred embodiments, in step (2), the amount of the refining flux added is 0.07-0.10 g / cm relative to the surface area of ​​the high chromium alloy cast iron liquid. 2 ; and / or, the refining flux is in powder form with a particle size of 0.5-1 mm.

[0018] In some preferred embodiments, in step (3), the centrifugal rotation rate of the cavity is 200-300 rpm, and / or the casting temperature of the low alloy steel is 1550-1600°C, preferably 1550-1580°C, and further preferably 1565-1580°C.

[0019] In some preferred embodiments, in step (1) and step (3), the high chromium alloy cast iron and the low alloy steel are both poured into the mold through the upper part of the mold cavity.

[0020] In some preferred embodiments, step (3) further comprises: after the temperature of the composite material obtained after the casting is lower than 200° C., removing the casting riser and the system used for casting, and then machining to remove inclusions on the upper end surface of the composite material.

[0021] The second aspect of the present invention provides a wear-resistant metal composite cone produced by the production method described in the first aspect.

[0022] The present invention adopts a centrifugal casting method to cover the surface of the high-chromium alloy cast iron melt with a refining flux of a specific composition, so that the hard slag shell can form low-melting-point slag, and inert gas is passed through the casting process of the high-chromium alloy cast iron and the low-alloy steel to achieve air isolation. Under the action of centrifugal force, the low-melting-point slag can quickly float in the subsequent casting process of the low-alloy steel, eliminating defects such as interface pores, non-metallic inclusions, looseness, porosity, cracks, etc., thereby improving the interface bonding strength and improving the wear resistance and safety of the cone. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0024] Figure 1 It is a structural schematic diagram of a casting centrifuge according to a specific embodiment of the present invention.

[0025] Figure 2 It is a schematic diagram of casting high chromium alloy cast iron according to the present invention.

[0026] Figure 3 It is a schematic diagram of the present invention covering the refining solvent.

[0027] Figure 4 Schematic diagram of casting low alloy steel according to the present invention.

[0028] Figure 5 It is a schematic diagram of the solidification of the wear-resistant metal composite cone of the present invention.

[0029] Figure 6 This is a scanning electron microscope image of the interface of the composite cone of Example 1 of the present invention.

[0030] Figure 7 This is a scanning electron microscope image of the interface of the composite material obtained in Example 1 without adding a refining flux and without introducing argon gas.

[0031] Figure 8 This is a scanning electron microscope image of the interface of the composite material obtained in Example 1 without adding a refining flux and without introducing argon gas.

[0032] Fig. 9 This is a scanning electron microscope image of the interface of the composite material obtained in Comparative Example 2.

[0033] Fig.10 This is a scanning electron microscope image of the interface of the composite material obtained in Comparative Example 3.

[0034] Description of Reference Numerals

[0035] 1. Outer ring of the cavity, 2. Metal chassis, 3. Cover plate, 4. Runner, 5. Cavity, 6. Melt casting ladle, 7. High chromium alloy cast iron melt, 8. Refining flux, 9. Low alloy steel melt, 10. Interface, 11. High chromium alloy cast iron, 12. Low alloy steel, 13. Inclusions. DETAILED DESCRIPTION

[0036] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0037] The first aspect of the present invention provides a method for preparing a wear-resistant metal composite cone, comprising the following steps: under the action of centrifugal force,

[0038] (1) casting high chromium alloy cast iron into a cavity of a casting centrifuge, and introducing an inert gas into the cavity;

[0039] (2) then covering the surface of the high chromium alloy cast iron liquid in the cavity into which the inert gas is introduced with a refining flux;

[0040] (3) subsequently casting low alloy steel;

[0041] The chemical composition of the refining flux includes, by mass percentage, 15-20% Na2O, 5-10% K2O, 10-15% SiO2, 2-5% resin, and 50-68% B2O3.

[0042] The present invention adopts a refining flux with a specific composition, wherein an appropriate amount of B2O3, Na2O, and K2O form a low-melting-point glass phase with oxides in a hard slag shell, which is beneficial to casting a low-alloy steel melt to cause the slag to break and achieve surface contact with a high-chromium alloy cast iron melt; an appropriate amount of resin burns and consumes oxygen in the air under the action of heat to block the air from contacting the high-chromium alloy cast iron liquid surface to form an oxide slag, and an atmosphere layer with a low oxygen content is formed on its liquid surface to prevent further oxidation of the high-chromium alloy cast iron liquid surface; an appropriate amount of SiO2 can regulate the viscosity of the glass slag, which is beneficial for glass phase inclusions to float to the upper end face of the cone under the action of centrifugal axial force; the components cooperate with each other to enable the hard slag shell to break quickly at a relatively low temperature and float under the action of centrifugation, and to form a low-oxygen atmosphere layer on the surface of the high-chromium alloy cast iron liquid surface to prevent oxidation; and the introduction of inert gas can further reduce the air content in the cavity and reduce slag. Under the same conditions, if the Na2O and K2O contents are too high, the viscosity of the glass phase slag is low, which can easily lead to the formation of slag inclusions in the low alloy melt and high chromium alloy cast iron under the action of centrifugal force.

[0043] Preferably, the chemical composition of the refining flux includes, by mass percentage, 17-20% Na2O, 7-10% K2O, 12-15% SiO2, 3.5-5% resin, and 50-60.5% B2O3. This preferred solution is more conducive to improving the service life and interface bonding strength, and further reducing the shedding of the composite layer.

[0044] The inert gas mentioned in the present invention includes argon, helium and the like.

[0045] In the present invention, the type of the resin can be selected from a wide range, as long as it can consume oxygen in the air; illustratively, it can be epoxy resin, phenolic resin, furan resin, etc., which are all commercially available and will not be described in detail here.

[0046] It is understood that steps (1) to (3) are all performed under the centrifugal action of the cavity, and in step (1), under the action of centrifugal force, the high chromium alloy cast iron melt will rise along the inner wall of the casting centrifuge cavity and cover the cavity wall to the required thickness. Those skilled in the art can select the casting amount of the high chromium alloy cast iron according to the required thickness.

[0047] In some preferred embodiments, in step (1) and step (3), the high chromium alloy cast iron and the low alloy steel are both poured into the mold through the upper part of the mold cavity.

[0048] Those skilled in the art can select the structure of the casting centrifuge according to actual needs. Figure 1As shown, the outer ring 1 of the cavity of the casting centrifuge is made of a metal mold and installed on a rotatable metal chassis 2. There is a metal mold cover plate 3 on the outer ring 1 of the cavity, and a runner 4 with a diameter of 200-300mm in the middle for casting; the outer ring 1 of the cavity, the metal chassis 2, and the cover plate 3 surround a molding cavity 5.

[0049] In some preferred embodiments, in step (1), the casting temperature of the high chromium alloy cast iron is 1400-1490°C.

[0050] In some preferred embodiments, in step (1), the centrifugal rotation rate of the cavity is 300-500 rpm.

[0051] In some preferred embodiments, step (1) further comprises: preheating the cavity wall to 200-300° C. before casting. The preferred solution of the present invention can slow down the surface solidification speed, which is more conducive to improving the surface finish of the cone.

[0052] In some preferred embodiments, in step (1) and step (2), the flow rate of the inert gas introduced into the cavity is 8-50 liters / minute, preferably 40-50 liters / minute, preferably 48-50 liters / minute. The preferred embodiment of the present invention can further reduce the air content in the cavity and the slag, thereby being more conducive to eliminating defects such as interface pores, non-metallic inclusions, looseness, pores, cracks, etc., improving the interface bonding strength, and improving the wear resistance of the cone.

[0053] In some preferred embodiments, in step (2), the centrifugal rotation rate of the cavity is 100-200 rpm.

[0054] In some preferred embodiments, in step (2), the refining flux is introduced 40-80 seconds after casting the high chromium alloy cast iron, preferably 40-60 seconds, and more preferably 50-60 seconds. According to the preferred embodiment of the present invention, the refining flux is introduced at an appropriate time after casting the high chromium alloy cast iron, which can prevent the high chromium alloy cast iron from further oxidation, and is more conducive to improving the interface bonding strength and the wear resistance of the cone.

[0055] In some preferred embodiments, in step (2), the amount of the refining flux added is 0.07-0.10 g / cm relative to the surface area of ​​the high chromium alloy cast iron liquid. 2 .

[0056] In some preferred embodiments, in step (2), the refining flux is in powder form with a particle size of 0.5-1 mm. In this preferred embodiment, the refining flux is in powder form for easy spraying, and its appropriate particle size is more conducive to promoting the rapid formation of low-melting-point slag from the hard slag shell.

[0057] Those skilled in the art can select the preparation method of the refining flux according to the needs, as long as it has the above composition. Preferably, the refining flux is obtained by the following method: mixing water glass according to the amount of Na2O and SiO2, grinding and mixing the water glass and other components evenly, drying and crushing.

[0058] In the present invention, it should be understood that inert gas is continuously introduced into the mold cavity during the casting of the low alloy steel in step (3). After the casting of the low alloy steel in step (3), inert gas is not introduced into the mold cavity.

[0059] In some preferred embodiments, in step (3), the centrifugal rotation rate of the cavity is 200-300 rpm.

[0060] In some preferred embodiments, the casting temperature of the low alloy steel is 1550-1600° C., preferably 1550-1580° C., and more preferably 1565-1580° C. The preferred embodiment of the present invention can reduce the stress between high chromium alloy cast iron and low alloy steel, and is more conducive to improving the interface bonding strength and the wear resistance of the cone.

[0061] Those skilled in the art may also adopt other conventional process steps to prepare metal wear-resistant composite materials. For example, step (3) may also include: after the temperature of the composite material obtained after the casting is lower than 200°C, then processing to remove inclusions on the upper end surface of the composite material; and then performing optional heat treatment. The obtained wear-resistant metal composite cone products include grinding rollers, rolling rollers, cones, etc.

[0062] The solidified composite material obtained by the preparation method of the present invention can eliminate interface pores and non-metallic inclusions, purify the interface, and is conducive to eliminating looseness, pores, cracks and other casting defects in the service area.

[0063] The second aspect of the present invention provides a wear-resistant metal composite cone produced by the production method described in the first aspect.

[0064] The present invention is further elaborated in detail below in conjunction with specific embodiments. Among them, the interface strength is measured by the tensile strength test method. The service life is measured by a three-body abrasive wear test. Specifically, the three-body abrasive wear test is carried out on a three-body wear testing machine, which is mainly composed of a motor, a spindle, a loading weight, a loading guide mechanism, a sample clamping mechanism, a rail, a sand collection mechanism, a dust prevention mechanism and a control system. It is an existing device; wherein the outer diameter of the rail material is 400mm and the width is 20mm. The spindle speed is 1r / min-90r / min steplessly adjustable, and the load is loaded by weights. The maximum load of a single axis is 5kg. Abrasives can be selected according to different wear and tear industries and mines. The present invention uses quartz sand with a hardness of HV1000-1200 and a particle size of 60-120 mesh; generally speaking, the wear resistance of a material can be expressed in the form of mass loss, volume loss, wear rate and relative wear resistance; the present invention is expressed in terms of relative wear resistance.

[0065] Example 1

[0066] (1) Figure 2 As shown, a high chromium alloy cast iron (chromium content by mass is 15%) melt 7 is poured into the cavity 5 through the runner 4 of the centrifuge upper cover plate 3 by a melt casting ladle 6. Under the action of centrifugal force, the high chromium alloy cast iron melt 7 rises along the inner wall of the centrifuge cavity 5 and covers the cavity wall to the required thickness. The wall of the centrifuge cavity 5 is preheated to 210°C in advance, the casting temperature is 1490°C, the centrifugal rotation rate is 350 rpm, and 45 liters / minute of argon is introduced into the cavity 5.

[0067] (2) 45 seconds after casting high chromium alloy cast iron, Figure 3 As shown, the surface is covered with a refining flux 8, the amount of which is 0.075 grams per square centimeter of the surface area of ​​the high chromium alloy cast iron liquid, the refining flux 8 is in powder form, the particle size is 0.5-1 mm, the centrifugal rotation rate is 150 rpm, and argon is introduced into the cavity at 45 liters per minute. The chemical composition of the refining flux is calculated by mass percentage: 16% Na2O, 6% K2O, 11% SiO2, 3% resin (specifically phenolic resin), and the balance is B2O3.

[0068] (3) Figure 4 As shown, low alloy steel melt 9 is poured into the runner 4, the casting temperature is 1560°C, and the centrifugal rotation rate is 220 rpm. Figure 5 As shown, the composite cone is below 200°C, and then the inclusions 13 on the upper end face and inner surface of the cone are removed by processing. The wear-resistant composite material casting is heat treated at 950°C for quenching and tempered at 450°C to obtain a wear-resistant composite material grinding roller product. The electron microscope image of the interface 10 is shown in FIG. Figure 6 As shown, it can be seen that the interface between the low alloy steel 12 and the high chromium alloy cast iron 11 diffuses mutually and the interface bonding is good.

[0069] The test results show that the interface bonding strength of the wear-resistant composite material grinding roller of this embodiment reaches 600MPa, and the composite layer falls off by 0.2%; the service life is increased by 50% compared with the comparative example 1 without adding refining flux and introducing argon gas under the same conditions.

[0070] Example 2

[0071] The method of Example 1 is referred to, except that the refining flux composition is: 17.5% Na2O, 7.5% K2O, 11% SiO2, 3% resin, and the balance is B2O3.

[0072] The same test results show that the interface bonding strength of the wear-resistant composite material grinding roller of this embodiment reaches 650MPa, and the composite layer falls off by 0.1%; the service life is increased by 50% compared with the comparative example 1 without adding refining flux under the same conditions.

[0073] Example 3

[0074] The method of Example 1 is used, except that the refining flux composition is: 16% Na2O, 6% K2O, 12.5% ​​SiO2, 3.5% resin, and the balance is B2O3.

[0075] The same test results show that the wear-resistant composite material grinding roller interface bonding strength of this embodiment reaches 645MPa, and the composite layer falls off by 0.09%; the service life is increased by 50% compared with the comparative example 1 without adding refining flux under the same conditions.

[0076] Example 4

[0077] The method of Example 1 is referred to, except that the refining flux composition is: 17.5% Na2O, 7.5% K2O, 12.5% ​​SiO2, 3.5% resin, and the balance is B2O3.

[0078] The same test results show that the wear-resistant composite material grinding roller of this embodiment has an interface bonding strength of 670 MPa, and the composite layer falls off by 0.05%. The service life is increased by 55% compared with the comparative example 1 without adding refining flux under the same conditions.

[0079] Example 5

[0080] The method of Example 4 is used, except that 50 seconds after casting the high chromium alloy cast iron, the surface is covered with a refining flux.

[0081] The same test results show that the wear-resistant composite material grinding roller of this embodiment has an interface bonding strength of 660 MPa, and the composite layer falls off by 0.06%. The service life is 50% longer than that of the comparative example 1 without adding refining flux under the same conditions.

[0082] Example 6

[0083] The method of Example 4 is used, except that the casting temperature of the low alloy steel melt is 1565°C.

[0084] The same test results show that the wear-resistant composite material grinding roller of this embodiment has an interface bonding strength of 680 MPa, and the composite layer falls off by 0.04%. The service life is 50% longer than that of the comparative example 1 without adding refining flux under the same conditions.

[0085] Example 7

[0086] The method of Example 4 is followed, except that the amount of argon introduced in step (1) and step (2) is 50 L / min.

[0087] The same test results show that the interface bonding strength of the wear-resistant composite material grinding roller of this embodiment reaches 675MPa, and the composite layer falls off by 0.07%; the service life is increased by 50% compared with the comparative example 1 without adding refining flux under the same conditions.

[0088] Example 8

[0089] The method of Example 7 is referred to, except that 50 seconds after casting the high chromium alloy cast iron, the surface is covered with a refining flux; and the casting temperature of the low alloy steel melt is 1565°C.

[0090] The same test was carried out, and the results showed that the interface bonding strength of the wear-resistant composite material grinding roller of this embodiment reached 700MPa, and the composite layer did not fall off; the service life was increased by 60% compared with the comparative example 1 without adding refining flux under the same conditions.

[0091] Example 9

[0092] The method of Example 8 is referred to, except that 80 seconds after casting the high chromium alloy cast iron, the surface is covered with a refining flux.

[0093] The same test results show that the wear-resistant composite material grinding roller of this embodiment has an interface bonding strength of 550 MPa, and its composite layer falls off by 2%. The service life is 20% longer than that of the comparative example 1 without refining flux under the same conditions.

[0094] Example 10

[0095] The method of Example 8 is used, except that the casting temperature of the low alloy steel melt is 1600°C.

[0096] The same test results show that the wear-resistant composite material grinding roller of this embodiment has an interface bonding strength of 600 MPa, and its composite layer falls off by 1.5%; the service life is increased by 15% compared with the comparative example 1 without adding refining flux under the same conditions.

[0097] Embodiment 11

[0098] The method of Example 8 is followed, except that the amount of argon introduced in step (1) and step (2) is 8 L / min.

[0099] The same test results show that the wear-resistant composite material grinding roller of this embodiment has an interface bonding strength of 500 MPa, and its composite layer falls off by 3%; the service life is 20% longer than that of the comparative example 1 without adding refining flux under the same conditions.

[0100] Comparative Example 1

[0101] The method of Example 1 is followed, except that no refining flux is added.

[0102] The interface electron microscopy image of the composite material obtained is shown in Figure 7 and Figure 8 As shown, it can be seen that slag inclusions appear at its interface, and the composition of the slag inclusions is C11.57wt%, O 22.11wt%, Si0.50wt%, Cr 14.07wt%, Mn 2.89wt%, Fe47.70wt%, Al 1.16wt%. And the high chromium alloy cast iron part has cracks.

[0103] The same test was carried out, and the results showed that the interface bonding strength of the composite material hammer head of this comparative example reached 450 MPa, and the composite layer fell off by 10%.

[0104] Comparative Example 2

[0105] The method of Example 8 is referred to, except that the refining flux composition is: 22% Na2O, 12% K2O, 12.5% ​​SiO2, 3.5% resin, and the balance is B2O3.

[0106] The interface diagram of the composite material obtained is shown in Fig. 9 As shown, it can be seen that the high chromium alloy cast iron is mixed into the low alloy steel.

[0107] The same test results show that the wear-resistant composite material grinding roller interface bonding strength of this comparative example reaches 590MPa, and the composite layer falls off by 1.4%; the service life is increased by 30% compared with the comparative example 1 without adding refining flux under the same conditions.

[0108] Comparative Example 3

[0109] The method of Example 8 is used, except that the refining flux composition is: 17.5% Na2O, 7.5% K2O, 20% SiO2, 3.5% resin, and the balance is B2O3.

[0110] The interface diagram of the composite material obtained is shown in Fig.10 As shown, it can be seen that the interface inclusions have compositions of C18.28wt%, O 22.68wt%, Si 46.15wt%, Cr10.58wt%, and Fe 2.31wt%.

[0111] The same test results showed that the wear-resistant composite material grinding roller interface bonding strength of this comparative example reached 490MPa, and the composite layer fell off by 3.5%; the service life was increased by 15% compared with the comparative example 1 without adding refining flux under the same conditions.

[0112] It can be seen from the above embodiments and comparative examples that the composite material obtained by the embodiments of the present invention has good interface bonding, no inclusions on the interface, high interface bonding strength, long service life, and significantly less composite layer shedding and no cracks.

[0113] Further, it can be seen from Examples 4 and 5, 8 and 9, 8 and 10, 4 and 6, 7 and 8 that the preferred timing of introducing the refining flux according to the present invention, or the preferred casting temperature of the low alloy steel melt according to the present invention, is more conducive to improving the service life and interface bonding strength, and further reducing the shedding of the composite layer. It can be seen from Examples 4 and 7, 8 and 11 that the preferred argon gas introduction amount according to the present invention is more conducive to improving the service life and interface bonding strength, and further reducing the degree of shedding of the composite layer.

[0114] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a wear-resistant metal composite cone, characterized in that: The following steps are involved: Under the action of centrifugal force, (1) casting high chromium alloy cast iron into a mold cavity of a casting centrifuge, and introducing an inert gas into the mold cavity; the casting temperature of the high chromium alloy cast iron is 1400-1490° C.; (2) then covering the surface of the high chromium alloy cast iron liquid in the mold cavity into which the inert gas is introduced with a refining flux, wherein the refining flux is introduced 40-80 seconds after casting the high chromium alloy cast iron; (3) subsequently casting low alloy steel, wherein the casting temperature of the low alloy steel is 1550-1600° C.; The chemical composition of the refining flux includes, by mass percentage, 15-20% Na2O, 5-10% K2O, 10-15% SiO2, 2-5% resin, and 50-68% B2O3.

2. The preparation method according to claim 1, characterized in that: In step (1), the centrifugal rotation rate of the cavity is 300-500 rpm.

3. The preparation method according to claim 1 or 2, characterized in that: Step (1) also includes: preheating the cavity wall to 200-300° C. before casting.

4. The preparation method according to claim 1, characterized in that: In step (1) and step (2), the flow rate of the inert gas introduced into the cavity is 8-50 liters / minute.

5. The preparation method according to claim 1, characterized in that: In step (2), the centrifugal rotation rate of the cavity is 100-200 rpm.

6. The preparation method according to claim 1, characterized in that: In step (2), the amount of the refining flux added is 0.07-0.10 g / cm relative to the surface area of ​​the high chromium alloy cast iron liquid. 2 .

7. The preparation method according to claim 1 or 6, characterized in that: In step (2), the refining flux is in powder form with a particle size of 0.5-1 mm.

8. The preparation method according to claim 1, characterized in that: In step (3), the centrifugal rotation rate of the cavity is 200-300 rpm.

9. The preparation method according to claim 1, characterized in that: In step (1) and step (3), the high chromium alloy cast iron and the low alloy steel are poured into the mold through the upper part of the mold cavity.

10. A wear-resistant metal composite cone obtained according to the preparation method according to any one of claims 1 to 9.